Strategi Pertahanan Indonesia: Pelajaran Dari Kekalahan Iraq Dalam Perang Teluk II 1990-1991 - Yusup Imannurdin; Aries Sudiarso; Dohar Sianturi (UNIVERSITAS PGRI YOGYAKARTA, 2023)
Abstract This study aims to analyze Iraq's defeat in the Second Gulf War in 1990-1991 and identify the defense strategy used by that country. In a global context that continues to develop, it is important for Indonesia as an archipelagic country with a strategic position in Southeast Asia to strengthen its defense capabilities and learn valuable lessons from the experiences of other countries. Through a qualitative descriptive literature study approach, this study analyzes the causes of Iraq's defeat in the Second Gulf War and the impact of the strategies they implemented. The Middle East as a conflict area rich in natural resources, especially oil, offers valuable lessons for Indonesia in understanding political dynamics and diversity which are potential threats in maintaining national security. The results of the study show that the international coalition that provided support and pressure on Iraq, as well as violations of international law committed by Iraqi troops when they attacked Kuwait, were the key factors that led to Iraq's defeat. This research also highlights the importance of support from the international community in maintaining regional stability and security. In conclusion, it is important for Indonesia to learn from Iraq's experience in the Second Gulf War to strengthen its national defense strategy. By observing the weaknesses that led to Iraq's failure, Indonesia can anticipate potential threats and develop defense strategies that are more effective, adaptive and based on international support. Keywords: Defense Strategy, Defeat of Iraq, Literature Study, National Security